Community education as a lifelong learning to support sustainable tourism - Murniati, Dewi Eka; Abdul Razzaq, Abdul Rasid; Nopembri, Soni; Abdul Hamid, Abdul Kharim; Paryono, Paryono (Jurnal Cakrawala Pendidikan, 2024)
A community-based tourism (CBT) approach has become an integral part of rural and sustainable tourism development strategies. However, CBT has some constraints on being sustainable due to some internal weaknesses and external concerns, including poor marketing competencies. As a top-down government initiative, Malaysian CBT homestay is blessed with numerous assistance to ensure its survival which in the other hand, creates over-reliance toward other parties. This lack of marketing expertise challenges homestay sustainability. This study examines the importance of community education in marketing activities as a lifelong learning towards sustainable tourism in Malaysia. Qualitative case study is employed to gain an extensive and in-depth explanation on homestay's marketing implementation and its issues. A semi-structured interview was taken to 9 homestay operators. This study employs a thematic data analysis to investigate the interview results. Research findings show that in majority, the community enjoys the comfort zone provided by government and travel agents, hence encourage the resistance for change. However, a few homestay demonstrates positive respond to involve lifelong learning through community education to support sustainable tourism. More importantly, partnership between various key stakeholders are the utmost important to ensure policy planning and to improve community education quality.